2009
DOI: 10.1073/pnas.0907032106
|View full text |Cite
|
Sign up to set email alerts
|

Auditory plasticity and speech motor learning

Abstract: Is plasticity in sensory and motor systems linked? Here, in the context of speech motor learning and perception, we test the idea sensory function is modified by motor learning and, in particular, that speech motor learning affects a speaker's auditory map. We assessed speech motor learning by using a robotic device that displaced the jaw and selectively altered somatosensory feedback during speech. We found that with practice speakers progressively corrected for the mechanical perturbation and after motor lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
88
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 94 publications
(98 citation statements)
references
References 36 publications
9
88
1
Order By: Relevance
“…Furthermore, shifts in perception were found to correlate with motoric adaptation, not auditory exposure, as found by Nasir and Ostry (2009) and Mattar et al (2011), and no consistent changes in perceptual function were found in two groups of passive listeners (exp. 2).…”
Section: Discussionmentioning
confidence: 49%
“…Furthermore, shifts in perception were found to correlate with motoric adaptation, not auditory exposure, as found by Nasir and Ostry (2009) and Mattar et al (2011), and no consistent changes in perceptual function were found in two groups of passive listeners (exp. 2).…”
Section: Discussionmentioning
confidence: 49%
“…Speech motor learning appears to alter auditory perception of speech (Nasir and Ostry 2009; Shiller et al. 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In an experiment Nasir and Ostry (2009) developed a robotic device which applied a mechanical load to the jaw and displaced the natural position of the jaw whilst participants were asked to articulate certain utterances. Results demonstrated that the participants who adapted to the new motor commands showed a perceptual shift while those who did not showed no perceptual shift (Nasir and Ostry, 2009). …”
Section: Perception Influenced By the Production Of Vocalizationmentioning
confidence: 99%